Incentives for cooperation in groups: sociality meets decision rights - Britta Butz; Pablo Guillen Alvarez; Christine Harbring (Review of Managerial Science, 2023)
We investigate the effect of a donation incentive tied to contributions to a public good when group members can decide on the size of their donation. An up to 20% donation of the public good was implemented either exogenously or endogenously by group members. In the Vote treatment, groups could either decide in favor of or against a donation of 20% of the public good; in the Vote Share treatment, subjects could decide on a donation share of between 0 and 20%. Results show that a large percentage of the participants vote in favor of implementing a donation share in both treatments. In groups voting in favor of a 20% donation share or endogenously implementing a high donation share in the Vote Share treatment contributions to the public good are higher compared to an exogenously implemented donation share.
Keywords: C72; C92; D64; D70; J33; M52; 650; Donations; Decision right; Public good game; Team incentives; Laboratory experiment; Charitable giving